CHILDFREE CHOICE IN THE DIALECTIC BETWEEN HUMAN RIGHTS AND ISLAMIC LAW: Navigating Bodily Autonomy and Hifz al-Nasl - Hasan, Ibnu Paqih (MAQASHID, 2025)
The decision to remain childfree has raised complex ethical and legal debates between the human rights principle of bodily autonomy and Islamic law, which emphasizes hifz al-nasl (preservation of lineage) as part of maqasid al-syariah. This study critically addresses the question: “can the childfree choice be ethically and legally justified within Islamic legal discourse, or does it inherently conflict with maqasid al-syariah?. Using a normative-juridical method and conceptual analysis, this research examines classical Islamic legal sources alongside international human rights instruments (UDHR, ICCPR, and CEDAW), interpreted through Jasser Auda’s sistems theory. The findings reveal that under specific ‘illat al-hukm (legal causes)-such as grave health concerns-the decisions to be childfree may be justified within Islamic frameworks. Jasser Auda reinterprets hifzh al-nasl as promoting care for the family’s well-being. The principle includes generational continuity, quality of life, and relationship. Auda’s expands hifzh al-nafs and hifz al-‘ird to include human dignity and human rights. Consequently, the decision to be  childfree can be interpreted as a manifestation of ethical rensponsibility, aligning with both Islamic values and the principles of inclusive human rights norms.